"Asthma can take over your life but having the right support makes that easier to deal with." Informing research priorities by exploring the barriers and facilitators to asthma control: a qualitative analysis of survey data. Issue 1 (December 2015) - Normansell, Rebecca; Welsh, Emma
Abstract Background Involving patients and the public in research prioritisation is important. Cochrane Airways works with authors to produce systematic reviews of evidence related to chronic airways disease. Cochrane Airways has undertaken activities to identify research priorities, including workshops with stakeholders and consultation with experts. We present the findings of an online survey, designed to align our work with the priorities of people affected by asthma. Methods We promoted a survey comprising open-ended questions via social media to people affected by asthma. We compiled the free-text responses and conducted an exploratory thematic analysis to identify important barriers and facilitators to asthma control. We triangulated findings with other research prioritisation activities to produce new review questions. Results We received 57 survey responses. Eight main themes emerged, most encompassing both facilitators and barriers: attitudes and knowledge; financial costs; environmental factors and triggers; healthcare systems; lifestyle factors; medication; self-care; and support. Barriers were more frequently mentioned than facilitators and many related to healthcare systems. Conclusions These findings offer valuable insights into the challenges faced by individuals affected by asthma in the UK, and possibly further afield. We developed a list of priority reviews based on what was said by people in this survey and at a workshop. This demonstrates the real impact that people affected by asthma have on the research agenda of Cochrane Airways. Over the next 2–3 years we will produce reviews that address some of these questions hopefully leading to health benefits.